Energy and nutrient intakes among Sri Lankan adults - Jayawardhan, R.; Thennakoon, S.; Byrne, N.; Soares, Mario; Katulanda, P.; Hills, A. (iMedpub Limited, 2014)
Introduction: The epidemic of nutrition related non-communicable diseases such as type 2 diabetes mellitus and obesity has reached to epidemic portion in the Sri Lanka. However, to date, detailed data on food consumption in the Sri Lankan population is limited. The aim of this study is to identify energy and major nutrient intake among Sri Lankan adults. Methods: A nationally-representative sample of adults was selected using a multi-stage random cluster sampling technique. Results: Data from 463 participants (166 Males, 297 Females) were analyzed. Total energy intake was significantly higher in males (1913 ± 567 kcal/d) than females (1514 ± 458 kcal/d). However, there was no significant gender differences in the percentage of energy from carbohydrate (Male: 72.8 ± 6.4%, Female: 73.9 ± 6.7%), fat (Male: 19.9 ± 6.1%, Female: 18.5 ± 5.7%) and proteins (Male: 10.6 ± 2.1%, Female: 10.9 ± 5.6%). Conclusion: The present study provides the first national estimates of energy and nutrient intake of the Sri Lankan adult population.